The politics of memory - Druliolle, Vincent (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The article analyzes the policies adopted by states in order to remember their difficult pasts. After explaining how they relate to the struggle for the truth and symbolic reparation, a typology of these policies is presented. Although various actors often refer to the necessity to overcome the past or to turn over a new leaf and see the politics of memory as a tool to achieve this objective, the article argues that this idea should be questioned.